A Systematic Literature Review : Strategi Manajemen Resiko Fraud dan Pencucian Uang di Lembaga Keuangan Digital (Studi Kasus Implementasi Pendekatan Berbasis Resiko): A Systematic Literature Review : Strategi Manajemen Resiko Fraud dan Pencucian Uang di Lembaga Keuangan Digital (Studi Kasus Implementasi Pendekatan Berbasis Resiko) - Puspita, Dyah Rangga; Sakdiya, Robi’atus; Oktaviani, Mita (JOURNAL AKSES STIA MALANG, 2026)
The existence of technology that is growing rapidly makes opportunities for fraud and money laundering. In this case, it is very necessary for Digital Financial Institutions to supervise and establish regulations that have been made to minimise the occurrence of risks. The purpose of this research is to understand in depth how and why the risk approach is applied in an organisation or specific project. This research method uses systematic literature review (SLR) by collecting secondary data from several credible journal databases. The SLR method focuses on the Preferred Reporting Systeatics Reviews and Meta-Analysis (PRISMA) guidelines. The implementation of a good risk management system will make it easier for organisations to manage, identify and measure the risks that will be faced by organisations today or in the future. Indonesia is faced with many cases of money laundering, it is due to the lack of supervision of the internal control system which is the most important part of an organisation. There are several ways that organisations can reduce the occurrence of money laundering, one of which is to create tools to detect suspicious actions. This aims to improve efficiency within the organisation and help make it easier to manage the risks that occur without any intervention from third parties. It is necessary to implement supervision and a risk-based approach to all operational activities in the financial sector.